Tecnologias digitais e multiletramentos: projetos online no processo de internacionalização do ensino de inglês na educação básica em contexto brasileiro - Maria Elizabete Villela Santiago (2019)
Globalization, begun in the 20th century, has blurred borders, allowing a multidirectional flow of cultures, languages, knowledge and actions among peoples around the world. Simultaneously, continuous technological development enabled interactions independently of space and time constraints, generating information and service offerings and demands among individuals from anywhere in the world. The interactions arising from an increasingly global and digital society occur through the use of semiotic resources directly influenced by the social context. In order to understand and make use of the resources available in each context, a set of literacies that encompasses written and oral verbal language, static and moving visual language, and knowledge about digital technology is necessary. In a society, which is increasingly more internationalized and digital, literacies in English Language, dominant foreign language, and digital literacies are necessary for access to information and participation in new types of interaction. Despite the massive presence of EL in several contexts and its predominance as foreign language in Brazilian schools, its teaching, mainly in the Elementary Public Schools, is far below what is necessary to promote the internationalization of this segment of education in Brazil, our country. The purpose of this case study was to investigate the use of the e-pals environment for the development of multiliteracies of 6th grade students in a public school in Minas Gerais state through interactions between them and their English-speaking peers from different countries using text, image, audio and video resources in the development of collaborative poster design. The research, proposed here, sought to develop, through the application of Multiliteracies Pedagogy and Project-Based Learning, literacies that involve knowledge about the poster genre, including aspects of the Grammar of Visual Design and the critical analysis of their social context; the use of the epals interface; knowledge of LI, used in real interactions; manipulation of hardware and software for the production of multimodal texts; intercultural knowledge, collaborative work and active learning. Data collection had three main moments: (a) a questionnaire to survey the socioeconomic profile of students and digital, LE, intercultural and collaborative literacies, (b) the production process of personal presentation videos and posters designed by the students, as well as the evaluation rubrics for these items (c) the application of a self-assessment questionnaire to students at the end of the project. Despite the unforeseen events during the research, such as the lack of participation of foreign colleagues in most of the Interdisciplinary Poster Power Project and the need for adaptations in part of the activities developed with the participants, the results obtained were favorable to the use of online environments to promote the internationalization of Elementary Education. In other words, the results obtained also indicated the development of multimodal and multicultural literacies accompanied by literacies in LI, as well as competences related to active learning, through the processes of knowledge within learning by design. In this way, this research sought to contribute to future actions aimed at the internationalization of Elementary Education.